Flow and heat transfer behavior of hybrid nanofluid through microchannel with two different channels. (April 2021) - Vinoth, R.; Sachuthananthan, B.
Abstract: The current investigation compares the heat transfer and flow characteristics of an oblique finned microchannel heat sink (MCHS) having newly designed pentagonal, triangular cross-sections. The working fluids used are CuO/Water (0.3%), Al2 O3 /Water (0.3%) nanofluids and Al2 O3 -CuO/Water (0.3%) Hybrid nanofluid. The heat sink has a cross-sectional area of 80 × 48 mm 2 and the experimental study was carried out by varying the mass flow rate from 0.1 to 0.5 LPM with a constant heat flux of 50 kW/m 2 . The experimental results revealed that the heat transfer rate and pressure drop for the pentagonal channel increased by 12.3% and 16.5% respectively when compared to the triangular channel heat sink using hybrid nanofluids which can be credited to the secondary flow generated in the oblique finned pentagonal microchannel heat sink. Also with hybrid nanofluid, the heat transfer rate enhanced by 4.2% and 5.5% with pentagonal microchannel heat sink when compared to Cuo/Water and Al2 O3 /Water nanofluids respectively. The Performance Evaluation Criterion for the pentagonal microchannel heat sink is found to be 21.12% higher than the triangular microchannel heat sink using hybrid nanofluid. The thermal resistance was found to be less and the pumping power required was found to be high for pentagonal channel heat sink with hybrid nanofluid when compared to other combinations.